EFEKTIVITAS PROGRAM ASURANSI USAHA TANI PADI (AUTP) DALAM UPAYA PERLINDUNGAN PETANI DI KECAMATAN MENGWI, KABUPATEN BADUNG - Juniasih, Ni Made; Sastra Wijaya, Komang Adi; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2021)
The Rice Farming Insurance Program (AUTP) in Mengwi District is a form of government concern in providing protection to farmers who often experience losses due to crop failure. This study analyzes effectiveness of AUTP in Mengwi by using the effectiveness of Duncan which consists of indicators of goal achievement, integration, and adaptation. This research is descriptive qualitative. This research based on effectiveness of Duncan analysis shows that the AUTP program in Mengwi has not been fully effective because there are still several obstacles such as limited operational costs, low participation of AUTP with a premium of 20% paid by farmers, the minimum criteria for claiming is too high, benefits of AUTP have not been felt by all farmers, socialization has not been optimal, and there is a shortage of implementing officers. Keywords: Effectiveness, Rice Farming Insurance Program, Farmer Protection